PENGGALIAN PERUBAHAN PERILAKU REMAJA SELAMA PANDEMI COVID-19 - Forman Novrindo Sidjabat (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2022)
The problem of COVID-19 has caused a decline in the health of adolescents, one of the consequences of the social restrictions has had an impact on changing their behavior. Social restrictions that imposed due to the COVID-19 pandemic will have adverse effects on adolescent behavior and activities such as increased screen time, passive behavior, and increased sleep. This study aims to determine changes in adolescent behavior during the COVID-19 pandemic. This study was a descriptive study of 150 adolescents who were collected using a consecutive sampling technique using an online questionnaire and analyzed univariately. The results showed that during the COVID-19 pandemic there was an increase in student anxiety about the family's economic condition, reduced physical activity, use of social media, consumption of sugary foods and drinks, cigarettes, and alcohol. A family-based approach is needed to monitor adolescent behavior in order to stay active and divert stress on activities that are preferred by them.